CCL3L1 copy number, CCR5 genotype and susceptibility to tuberculosis - Carpenter, Danielle; Taype, Carmen; Goulding, Jon; Levin, Mike; Eley, Brian; Anderson, Suzanne; Shaw, Marie-Anne; Armour, John A.L. (BioMed Central, 2014)
Background: Tuberculosis is a major infectious disease and functional studies have provided evidence that both the chemokine MIP-1α and its receptor CCR5 play a role in susceptibility to TB. Thus by measuring copy number variation of CCL3L1, one of the genes that encode MIP-1α, and genotyping a functional promoter polymorphism -2459A > G in CCR5 (rs1799987) we investigate the influence of MIP-1α and CCR5, independently and combined, in susceptibility to clinically active TB in three populations, a Peruvian population (n = 1132), a !Xhosa population (n = 605) and a South African Coloured population (n = 221). The three populations include patients with clinically diagnosed pulmonary TB, as well as other, less prevalent forms of extrapulmonary TB. Methods and results: Copy number of CCL3L1 was measured using the paralogue ratio test and exhibited ranges between 0–6 copies per diploid genome (pdg) in Peru, between 0–12 pdg in !Xhosa samples and between 0–10 pdg in South African Coloured samples. The CCR5 promoter polymorphism was observed to differ significantly in allele frequency between populations (*A; Peru f = 0.67, !Xhosa f = 0.38, Coloured f = 0.48). Conclusions: The case–control association studies performed however find, surprisingly, no evidence for an influence of variation in genes coding for MIP-1α or CCR5 individually or together in susceptibility to clinically active TB in these populations.